PROBLEM MANUSIA DI ERA GLOBAL DAN SOLUSINYA - Ghani, Husain Abdul; Putri, Rizki Amelia; Purba, Asmat (Jurnal TEDC; Vol 20 No 1 (2026): JURNAL TEDCDO - 10.70428/tedc.v20i1.1483, 2026)
This study presents a comprehensive and in-depth analysis of the complexity of human problems in the contemporary era of globalization, characterized by multidimensional disruption phenomena. The primary objective of this paper is to dissect the social and psychological pathologies arising from the interaction between digital technological advancement, global economic integration, and the erosion of local cultural values. Through extensive literature review and analysis of recent secondary data from the 2023-2025 period, this research identifies that the "connectivity paradox" has spawned a global mental health crisis, where digital hyperconnectivity correlates directly with increased social isolation, self-alienation, and anxiety disorders. Furthermore, cultural homogenization has triggered severe identity crises among the youth, while economic pressures due to automation and global competition exacerbate inequality and existential insecurity. In response to this crisis, this paper formulates an integrative solution framework emphasizing the revitalization of local wisdom as an adaptive filter, character education reform oriented towards moral resilience, and structural policies that humanize technology. The analysis suggests that a synthesis of global insights and local wisdom roots is key to restoring human well-being and social cohesion amidst the currents of globalization.